URBAN POETICS AND SPATIAL REPRESENTATION IN 20TH-CENTURY AMERICAN LITERATURE - Shernazarova , Nigora (Scientific practical conference, 2026)
This extended thesis examines the poetics of urban space in 20th-century American literature through an interdisciplinary framework that integrates spatial theory, literary modernism, racial studies, and postmodern cultural analysis. The study argues that urban space in American fiction functions not merely as a physical backdrop but as a structural, symbolic, ideological, and psychological system shaping narrative form and subjectivity. Drawing on theoretical perspectives from Henri Lefebvre, Michel Foucault, Edward Soja, and Walter Benjamin, the research analyzes representations of the American metropolis in works by John Dos Passos, F. Scott Fitzgerald, Theodore Dreiser, Langston Hughes, Ralph Ellison, James Baldwin, Saul Bellow, Thomas Pynchon, Don DeLillo, Toni Morrison, and others. The thesis demonstrates that 20th-century American literature transforms the city into a dynamic narrative architecture reflecting capitalism, race, gender, alienation, and media saturation. The American city evolves from modernist fragmentation to postmodern simulation, becoming a laboratory of modern consciousness.